The corporate culture of a research university as an object of sociological analysis (The Journal of Psychology and Sociology, 2012)
The paper discusses the specific of the sociological study of the corporate culture of modern research university. By summarizing the results of studies by various authors clarifies the concept of corporate culture associated to the university as a special type of corporation. The corporate culture of the university is regarded as one of the ways to improve its com- petitiveness and means of coordinating the interests of higher education corporations with domestic and foreign public. In the paper analyzed the functions of corporate culture. Particular attention is paid to the methods of sociological research, which are included in the strategy of studying the corporate culture of the university.
Keywords: universities; corporations; corporate culture; methods of sociological research.